1995
DOI: 10.1680/gein.2.0029
|View full text |Cite
|
Sign up to set email alerts
|

Geosynthetic-Reinforced Soils Under Repeated Loading: A Review and Comparative Design Study

Abstract: Many types of geosynthetic-reinforced soil are subjected to repeated or cyclic loading. In transportation infrastructures such loading conditions occur in pavements supported by reinforced soil retaining walls, reinforced soil bridge abutments, reinforced roadways, or railway foundations. Insufficient knowledge on the mid- and long-term performance of geosynthetics and on soil-reinforcement interaction under such conditions might be considered a hurdle to their use as reinforcement in permanent earth structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 21 publications
6
9
0
Order By: Relevance
“…section 3 and section 5) were compared, it was observed that the effectiveness of a geogrid to reduce track settlement became higher for softer subgrades (Figure 5(a) and (b)). This observation is in agreement with the results of full-scale tests presented by Ashmawy and Bourdeau (1995). It was also observed that among the four types of geosynthetic used, the geogrid at section 3 performed most effectively.…”
Section: Vertical Deformations Of Ballastsupporting
confidence: 91%
“…section 3 and section 5) were compared, it was observed that the effectiveness of a geogrid to reduce track settlement became higher for softer subgrades (Figure 5(a) and (b)). This observation is in agreement with the results of full-scale tests presented by Ashmawy and Bourdeau (1995). It was also observed that among the four types of geosynthetic used, the geogrid at section 3 performed most effectively.…”
Section: Vertical Deformations Of Ballastsupporting
confidence: 91%
“…When the results for sections with similar geogrids are compared, it is observed that the effectiveness of a geogrid to reduce track settlement becomes higher for softer subgrades. This observation is in agreement with previous study by Ashmawy and Bourdeau [35].…”
Section: Vertical Strains In Ballastsupporting
confidence: 94%
“…Such an observation is in agreement with the results of full-scale tests presented by Ashmawy and Bourdeau (1995). It is also observed that among the four synthetic types used TerraGrid performed most effectively.…”
Section: Settlements Of Ballast Layersupporting
confidence: 91%